ASSESSMENT OF FARMERS PERCEPTION ON OIL DISCOVERY IN ALKALERI AND AKKO LOCAL GOVERNMENT AREAS OF BAUCHI AND GOMBE STATES, NIGERIA - Mazadu, Z. M.; Murtala, N.; Yakubu, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2023)
The study assessed farmers’ perception on oil discovery in Alkaleri and Akko Local Government Areas of Bauchi and Gombe States, Nigeria. Multi-stage sampling technique was used to select 200 respondents. Data were collected using structured questionnaire and analyzed using both descriptive and inferential statistics. The findings revealed that most (84.5%) of the respondents were males with mean age of 45 years. Also 64.0% were married with mean household size of 11 persons. The results also showed that 30% had attained tertiary education and 49.5% had farming experience of 6-10 years. About 60% inherited their farmland. The results further showed that, the respondents agreed that the rivers would be contaminated, air would be polluted, and farm land would be used for construction with mean scores of 4.7, 4.6 and 4.5 respectively. The perceived benefits according to the respondents include presence of electricity, better access road, and employment opportunities with mean scores of 4.1, 4.0 and 3.9 respectively. The regression results showed that age, educational level, annual income, access to credit and extension contact were significant (P<0.001). Also, marital status, household size and main occupation were significant (P<0.01) while land acquisition and source of agro input were significant (P<0.05) in influencing their perception on the oil discovery. The major perceived constraints were land destruction with 92%, water contamination 84%, reduction of farming activities 75% and deforestation 65% which were ranked 1st, 2nd, 3rd and 4th respectively. It was concluded that the respondents had the perception of the oil effects and benefits on their community and agricultural activities in general. Based on the findings, it was recommended that government and oil companies should hold a stakeholder meeting with the communities. Oil companies should plant more trees to replace the destroyed ones, also government and oil companies should ensure adequate security in the communities.